Electrochemical Reduction of Carbon Dioxide to Value‐Added Products: The Electrocatalyst and Microbial Electrosynthesis. Issue 7 (9th October 2018) - Chen, Zhipeng; Wang, Xiaohan; Liu, Licheng
Abstract: The electrochemical reduction of carbon dioxide (CO2 ) to value‐added products obtains great attention and investigation worldwide in recent years. The commercialization of this green process relies on the progress of relating high‐performance electrocatalysts and their feasibility with proper reactor design. The microbial electrosynthesis (MES) is an alternative route to reduce CO2 with electroactive bio‐film electrode as catalyst. This review presents the research status and development of cathode catalysts, particularly focusing on the active sites and development tendency, for highly efficient electrochemical reduction CO2 from personal viewpoint. Some of our results are also presented to exhibit contributions. MES shows a similar process to the typical electrochemical reduction of CO2 . Their combination is an important trend, and the future research in this field is full of challenges and opportunities. Abstract : Electrochemical reduction of CO2 to value‐added chemicals using renewable electricity offers a promising strategy to deal with rising CO2 emission and the energy crisis. This review combines the research results of our lab to present on the history, current situation, and development tendency of electrocatalysts for highly efficient electrochemical reduction CO2 .